The Phenomena of Code-Switching in Sociolinguistics Class At English Department Students STAIN Kediri - Aini, Nurul (Ali Muchasan, 2019)
In sociolinguistics field, one of the most popular language contact phenomena is the phenomena of Code-Switching. Code-switching is a kind of sociolinguistics phenomenon occurs when two or more languages exist in a conversation. A sociolinguist says that Code-Switching, that is switching back and forwarding between languages, even during the same utterances. This research conducts a sociolinguistics research especially in Code-Switching Phenomena to answer the following questions: What kind of Code-Switching in terms of utterance unit (words, phrases and clauses) used by the students in the eighth semester of Sociolinguistics Class at English Department STAIN Kediri? Why do the students use Ã¢â‚¬Å“Code-SwitchingÃ¢â‚¬Â in Communication? The researcher chooses this method is based on some characteristics of descriptive qualitative research methods that are appropriate for this research. The subject of the research is the students in the eight semester especially the students who join Sociolinguistics Class at English Department STAIN Kediri. They have to speak English in learning process. It can not be seen only from the case speaking but also how to speak English well and correctly.